Effect of the season on blood changes of oxidative stress index (OSi) in the Italian Mediterranean Buffalo (Bubalis bubalis - Giovanna De Matteis; Emanuela Rossi; Maria Chiara La Mantia; Roberto Steri; Vittoria Lucia Barile; David Meo Zilio (Revista Científica)
The oxidative stress index (OSi) has recently been used as a valid tool for providing an in-depth picture of redox status and oxidative stress. Previous studies in cattle showed that high temperatures increase the production of reactive oxygen species (ROS), causing an imbalance between ROS and the ability of antioxidant systems to detoxify and remove the reactive intermediates. As such studies remain limited in buffalo, the effect of temperature on oxidative stress was investigated through the OSi by combining the results of derivatives of reactive oxygen metabolites (d-ROMs) and biological antioxidant potential (BAP) in an Italian buffalo herd. Blood samples were collected from 40 buffaloes over 12 time points distributed in two years (2021, 2022). Samples were taken during hot and cold/mild seasons monthly. Plasma free oxygen radicals were determined using a d- ROMs test (Diacron, Italy) modified for a microplate procedure, and results were expressed in arbitrary Carratelli Units (U CARR). Plasma antioxidants were determined using the BAP test (Diacron) in a dedicated spectrophotometer (Carpe Diem Free, Diacron). The OSi parameter was calculated as d-ROMs/BAP*100. Temperature and humidity were recorded daily during the trial to calculate the Temperature Humidity Index (THI). The formula used was THI=(1.8*T-((1-Ur/100)*(T-14.3))+32), with T=temperature (°C) and Ur=relative humidity (%). The model included year and season and their interaction for statistical analysis. Results of this study showed for the first time the effect of the season on the oxidative stress in buffalo. The minimum and maximum THI values for the cold and hot seasons recorded during the experimental period were 29.6-74.5 and 54-85 in 2021 and 31.6-66.3 and 47.9-86.2 in 2022, respectively. Levels of d-ROMs and BAP were affected by season (133.0±3.67 vs 145.1±3.54 UCARR, p=0.0189, and 2489.19±32.51 vs 2392.43±31.33 mml/L, p=0.033, in hot and cold/mild season, respectively). Significant year*season interaction was found for d-ROMs and BAP (p=0.06 and p<0.0001, respectively). Moreover, OSi was affected by season, showing a growing trend from hot to cold season (5.35±0.15 vs 6.17±0.14, p<0.0001), but, interestingly, it was unaffected by annual variation. In conclusion, this field study showed that OSi could be considered a better and independent marker of oxidative status in buffalo concerning the evaluation of single determinations of d-ROMs and BAP.